(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Since 2023, the HELLO, SENIORS project has been taking place in the city of Kaunas, aimed at preventing falls and injuries. Residents of Kaunas aged 60 and over who participate in the project have the opportunity to take part in free and various physical activity programmes designed to reduce their risk of falls and injuries. Participants can choose from a variety of activities, including functional training, line dancing, Tai Chi sessions, aquatic exercises, and proper falling techniques training. In 2024, a study was conducted to evaluate the effectiveness of the physical activity programmes implemented within the HELLO, SENIORS project in Kaunas. The aim of the study was to examine the changes in physical performance indicators as a result of the activities, as well as to explore the relationships between physical performance and physical literacy, health literacy, mental health (signs of depression), and physical health (frailty syndrome). A total of 214 individuals participated in the study: 207 women and 7 men. Due to the small sample size of male participants, the analysis was based solely on the data from female participants. The average age of participants was 69.6 years. Most of them (56.7%) had a university-level education. The results showed that the physical activity programmes organised during the project had a significant positive impact on the physical capacity, psychological wellbeing, and health perception of older adults. Tai Chi sessions were found to be particularly effective. The study highlights the importance of physical literacy as a motivating and health-promoting factor.